Measurement of parent satisfaction in the paediatric intensive care unit – Translation, cultural adaptation and psychometric equivalence for the French-speaking version of the EMPATHIC-65 questionnaire - Grandjean, C.; Latour, Jos; Cotting, J.; Fazan, M.; Leteurtre, S.; Ramelet, A. (Churchill Livingstone, 2017)
Introduction: Within paediatric intensive care units (PICUs), only a few parent satisfaction instruments are validated and none are available for French-speaking parents. The aims of the study were to translate and culturally adapt the Dutch EMPATHIC-65 questionnaire into a French version and to test its psychometric equivalence. Methods: Two French-speaking PICUs in Switzerland and France participated. The questionnaire was translated using a standardised method and parents with PICU experience were interviewed to assess clarity of the translated version. Secondly, parents of children hospitalised for at least 24 hours and who were fluent in French, were invited to complete the French translated version of the EMPATHIC-65 questionnaire. Reliability and validity measures were used to examine its psychometric equivalence. Results: The overall mean clarity agreement reached 90.2% by 17 French-speaking parents. Eight unclear items have subsequently been reworded. One hundred seventy-two parents completed the French version questionnaire. Reliability and convergent validity have been confirmed by an adequate internal consistency (0.59–0.89) and convergent validity (rs 0.25–0.63, p < 0.01). Conclusion: Psychometric equivalence of the French EMPATHIC-65 questionnaire highlights the appropriateness of relying on available valid instrument to expand the availability of health instrument measure in French.